(untitled) (Melville, N.Y., 2003)
The dominant theme of the International Congress on Plasma Physics 2002 was the unity of plasma physics, covering all aspects, from low-temperature plasmas to fusion plasmas, from industrial applications to astrophysics, and all three approaches to investigating physical phenomena: experiment, observation, and theory/computation. Topics include: experiments on laboratory devices, low-temperature plasmas, magnetic confinement, inertial confinement and beams, plasma applications, and experimental simulation of phenomena observed in natural plasmas; plasma theory and simulation, kinetic theory and transport modeling, statistical mechanics, atomic, and molecular processes, macroscopic equilibrium and stability, waves and nonlinear dynamics, flowing and rapidly changing plasmas, and particle acceleration and transport; observations of natural plasmas, planetary atmospheres, ionospheres, and auroral regions, planetary magnetospheres and space weather, solar wind and outer heliosphere, and solar and coronal physics (Editorial Reviews)
Keywords: Plasma (Ionized gases)